Wenn das Böse wie das Gute aussieht... - Deselaers, Manfred (Horyzonty Wychowania, 2017)
On the example of Rudolf Höss, the commanding officer of Auschwitz,theauthor ponders over the fact how man, who was not a sadist by nature, man who was not mentally ill, who was a loving husband and father, could become the greatest perpetrator of genocide in history? He also gives some thought to the essence of a complete loss of humanity. Thecausesofsuchbehaviouraresoughtfirstofallinthenegativeexperiencesoflovetakenfromhome,whoseconsequence isbreakingoffanycontactswithfamily,withdrawingfromChurch and disavowing Catholic faith, and finally joining NSDAP (National Socialist German labour party). ThenextreasonforHöss’sbrutalconductisdiscernedbythe authorinthenational-socialistideologyheadopted.Accordingto theauthor,itisNazism,which limited people to animal-like conduct(intheliteralmeaningoftheword)anddeprivedthemofany dignityandfreedom,thatmadeHöss’sconscienceappeaseand drew out his sensitivity to other man’s suffering. TheauthorcontraststhecruelconductofthecommandingofficerofAuschwitzwithhishumanity.Heshowstheexistingtracesof goodness, which were supposed to become a sort of protest againstevil,whichwascausedbyhimandwhichshapedhiswork and conduct. His deliberations are based mainly on the period RudolfHössspentinprison.Theauthorstressesthatitwasthere thathisinternaltransformationtookplace,thepricksofconscience andtheawarenessofbrutalityappeared.ItwasonlyinPolishprisons,asaresultofhumanetreatment,thatHössfoundhishumanity,convertedintoCatholicismandapologizedforhiscrimes. Concluding, the author deliberates on whether one can talk about man’s guilt in the case he was wounded by improper Catholic upbringing as a child, then his conscience was drawnout by the national-socialist ideology, to finally discover his humanity and dignity anew in Polish prisons.